2015
DOI: 10.1021/acs.joc.5b01183
|View full text |Cite
|
Sign up to set email alerts
|

I2/KI-Mediated Oxidative N–N Bond Formation for the Synthesis of 1,5-Fused 1,2,4-Triazoles from N-Aryl Amidines

Abstract: An I2/KI-mediated oxidative N-N bond formation reaction is described. This new and environmentally benign approach allows for the convenient synthesis of a variety of 1,2,4-triazolo[1,5-a]pyridines and other 1,5-fused 1,2,4-triazoles from readily available N-aryl amidines in an efficient and scalable fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 33 publications
(64 reference statements)
1
30
0
Order By: Relevance
“…Previously,w ed isclosed an I 2 /KI-mediated oxidative NÀNb ond formation reactionf or the synthesis of 1,2,4-triazolo [1,5-a]pyri- Scheme1.Twop athways for the I 2 /KI-meditated oxidative cyclization of Naryl amidines 3. dines and relatedh eterocycles 4' from readily available N-aryl amidines 3 [10] (path a, Scheme1). However,u nder the previous oxidative cyclization conditions (I 2 /KI, K 2 CO 3 ,D MSO,1 00 8C), substrate 3a bearing ab enzylg roup at R 3 position resulted in no expected triazolopyridine (4a')a ta ll (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previously,w ed isclosed an I 2 /KI-mediated oxidative NÀNb ond formation reactionf or the synthesis of 1,2,4-triazolo [1,5-a]pyri- Scheme1.Twop athways for the I 2 /KI-meditated oxidative cyclization of Naryl amidines 3. dines and relatedh eterocycles 4' from readily available N-aryl amidines 3 [10] (path a, Scheme1). However,u nder the previous oxidative cyclization conditions (I 2 /KI, K 2 CO 3 ,D MSO,1 00 8C), substrate 3a bearing ab enzylg roup at R 3 position resulted in no expected triazolopyridine (4a')a ta ll (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noteworthy that when the substituents on the N ‐(2‐pyridyl)amidines are slightly different, even if the same oxidant was used, the intramolecular bonding modes to afford the corresponding products by C−H functionalization were diverse. For instance, in 2016, Chang's group published the synthesis of 2‐aminoimidazo[1,2‐α]‐pyridines through an I 2 /KI‐mediated intramolecular oxidative C−N bond formation of N ‐(2‐pyridyl)amidines (Scheme b), in which the bonding mode of the reaction was completely different from a previously reported one by Chang and co‐workers in 2015. Therefore, these surveys indicated clearly that the results of the reaction were greatly affected by the structure of the substrates and the reaction conditions.…”
Section: Introductionmentioning
confidence: 94%
“…In previous literature reports, as one of the most important N‐aryl amidines, N ‐(2‐pyridyl)amidines have also been employed for the synthesis of different nitrogen‐containing heterocyclic skeletons by using various oxidants by the C−H functionalization for N−N and C−N bond formation. For example, a literature survey indicated that when a large variety of oxidants were utilized, including air, PIFA (phenyliodine bis(trifluoroacetate)), NaClO, MnO 2 , Pb(OAc) 4 , and I 2 , 1,2,4‐triazoles with various substituents can be achieved by intramolecular oxidative N−N bond formation from N ‐(2‐pyridyl)amidines substrates (Scheme a). However, it is noteworthy that when the substituents on the N ‐(2‐pyridyl)amidines are slightly different, even if the same oxidant was used, the intramolecular bonding modes to afford the corresponding products by C−H functionalization were diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, utilizing molecular iodine as the sole oxidant, we have successfully constructed nitrogen‐containing heterocyclic frameworks, such as pyrazoles, quinazolinones, and benzimidazoles, through oxidative C−N bond formation . Recently, we disclosed an I 2 ‐mediated oxidative cyclization reaction of N ‐aryl amidines 8 to prepare 1,5‐fused 1,2,4‐triazoles 9 . As a continuation of this research into the synthesis of fused 1,2,4‐triazoles, herein we envisioned a sequential synthetic method for the preparation of 1,2,4‐triazolo[4,3‐ a ]pyridines and related heterocycles through condensation of aryl hydrazines and aldehydes followed by iodine‐mediated oxidative cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Recently,wedisclosed an I 2 -mediated oxidative cyclization reactiono fN-aryl amidines 8 to prepare 1,5-fused1 ,2,4triazoles 9. [24] As ac ontinuation of this research into the synthesis of fused 1,2,4-triazoles, herein we envisioned asequential synthetic method for the preparation of 1,2,4-triazolo[4, 3-a]pyridines and relatedh eterocycles through condensation of aryl hydrazines and aldehydes followed by iodine-mediated oxidative cyclization.…”
Section: Introductionmentioning
confidence: 99%